New record of anthopleura radians spano & Häussermann, 2017 (Cnidaria: Actiniaria: Actiniidae) from the Mexican Pacific - Vasallo Avalos, Aurora (2020)
As part of a biodiversity study on intertidal invertebrates, several sea anemones from the west coast of the Baja California Peninsula were collected in June 2016. The taxonomic features of four specimens agree well with those of the species Anthopleura radians, a recently described sea anemone from northern Chile. This study is the first published report on this species outside the range of distribution documented in the original description, including new images of A. radians’ external and internal features and complete characterization of their cnidae. Differences between A. radians from other species of the genus reported from the eastern Pacific are also discussed.